Understanding the Use of Information Communication Technology from the Church’s Missional Perspective - Joseph Owusu Atuahene; Isaac Boaheng (E-Journal of Humanities, Arts and Social Sciences, 2025)
The growth in science and technology in the 21st Century has deeply affected Christian ministry in many ways. Christian ministry, with its foundation in the Bible, can be well achieved with the help and use of a higher level of technological know-how as we have in this era, and the call by Jesus Christ to send the Gospel to the world is a call to technological inventions and usage. The emergence of communication technologies has brought a boost in Christian evangelism, using technology to easily reach the world with the Gospel using technologies such as television and radio broadcasts, print media, computers, and digital space. However, more must be done regarding the connection between digital space and Christian ministry. Therefore, this study sought to identify and discuss the practical connection between Christian ministry and technology. It emphasizes the urgent need for digitalizing Church ministry, provides a comprehensive understanding of technology from the church’s missional perspective, and identifies practical ways to engage with technology in its mission. This study is non-empirical research. Data were collected from existing publications and analyzed thematically. The main argument of this study is that Christian ministry can only be entirely successful by considering effective engagement with digital space. The study discovered that the rapid development of communication globally has influenced and affected the church’s mission, evangelism, and communication. It also found out that any institution, including the church in the 21st Century, that refuses to engage ICT in its activities effectively may cease to exist within the next ten years. This study contributes to the ongoing theological and missiological discourse on digital ecclesiology.